Implementation of Deep Learning in Religious Education Learning For The Internalization of Religious Values and The Formation of Religious Behavior - Ade Yuliyanti; Alfiah Khoerunnisa (IQRO: Journal of Islamic Education, 2026)
This study aims to analyze the implementation of deep learning-based Islamic Religious Education (PAI) learning and the internalization of religious values and religious behavior in students. This study used a mixed methods approach with a sequential explanatory design, namely the collection and analysis of quantitative data followed by qualitative data to strengthen and explain the research findings. Quantitative data were obtained through closed-ended questionnaires, while qualitative data were collected through open-ended questionnaires that explored the experiences, meanings, and changes experienced by students. The results show that deep learning-based PAI learning provides a memorable, enjoyable, and meaningful learning experience for students. The implementation of the deep learning approach to PAI learning is categorized as good, although the variety of learning methods is still categorized as needing improvement. These results indicate that the internalization of religious values has fostered an understanding of the practice of Islamic teachings in everyday life. PAI learning implementing a deep learning approach is effective in internalizing religious values and holistically shaping students' religious attitudes through active, contextual, reflective, and transformative learning.